Detection and Prevention of DNS Tunneling Attacks: Exploring Technologies and Methodologies - Inayat, Usman; Khan, Reamsha (UMT Artificial Intelligence Review, 2024)
DNS tunneling attack is one of the most common and ignored attacks that the current systems are vulnerable to. This study examines the functionality of DNS in terms of DNS hierarchy and the ways through which intruder creates a tunnel. The research used both rule-based and model-based technology tools alongwith other detection-based technologies, namely signature-based and threshold-based technologies. The graphical representation of the tunnel detection technology has been shown to better understand the systematic working of DNS. Based on the review of previous research methodologies, the current research analysed methods for the detection and prevention of DNS tunneling, which includes a location-based model using GPS and observing data packet sizes.